Implementasi Pendidikan Karakter Religious Dalam Membentuk Kepribadian Siswa Di Madrasah Tsanawiyah Miftahussalam Kecamatan Lumbang Kabupaten Probolinggo - Maulidiyah, Adiba; Muhammad, Devy Habibi; Syahrin, Muhammad Alfi (STIT Muhammadiyah Paciran Lamongan, 2022)
There are still many school-age children in rural areas who behave badly in the school environment and outside of school, for example, students have started to dare to say dirty words to their parents and do bad things to their friends. The purpose of the application of religious character education is expected to be a solution to the background of the problem above in forming good character towards students, so as to provide the expected results, especially in student behavior towards a better direction. The method used by the researcher is a qualitative research, where this method is more descriptive, the data collected is in the form of interview observations, namely opinions from sources, recordings, and other supporting documents. The results of the study explain the efforts of teachers in developing and shaping the character of madrasa students to become human beings who have good moral character, it is not as easy as one thinks, it takes quite a long time from several interviews carried out, integration in shaping the character of students, teachers carry out several programs such as school habituation activities, spontaneous school activities , exemplary and supervising the school and outside the school all of these activities went quite well seeing the support from the parents of the students and the enthusiastic spirit of the students in following them so that what was expected was achieved optimally.